Student-centredness in urban schools in China (UCL Press, 2014)
This study investigates how teachers understand and implement the emphasis on studentcentredness in the new English curriculum in secondary classrooms in urban areas of China and the factors affecting implementation. It focuses on whether the advantages (greater access to resources, better trained teachers, and so on) of the urban context make implementation easier than in rural areas. Data from lesson observations and reflective statements by teachers in urban schools show that their understanding of the notion of student-centredness is superficial and that the well-resourced urban schools find reform as challenging as rural schools.